Experiencia profesional adquirida en la empresa Cosmos Agengia Marítima SAC en el campamento Malvinas - Mattos Hidalgo, Elías Daniel (2022)
Work is one of the fundamental rights that every human being has (DIARIO OFFICIAL EL PERUANO, 1993 pp. 7, article 22), being the responsibility of the employer to provide safe conditions for its normal development, in order to prevent the occurrence of accidents at work for the benefit of the staff. Cosmos Agencia Marítima SAC staff is exposed to various hazards, including mechanical, electrical, chemical, physical, psychosocial, ergonomic and natural phenomena, these being of considerable potential for the occurrence of work accidents, for which Within its integrated management system, the organization has the IPERC matrices for jobs, with the aim that there are defined barriers within the activities, which allow the probability of workplace accidents to be reduced to a minimum. The work of eight (8) years of work experience in the company Cosmos Agencia Marítima SAC, allowed me to learn to develop the IPERC method, taking as reference the R.M N° 050-2013-TR, in the internal logistics operations that the organization provides. as a service to the company Pluspetrol Corporation SA, in the Malvinas camp, lot 88. Therefore, from the present professional sufficiency study, it was possible to strengthen the already existing IPERC matrices, considering hazards not initially identified and thereby not only cover the legal requirements that the Peruvian state demands, but also avoid the occurrence of accidents and the economic cost that this entails in case these happen.